The Cybernetic Revolution and the Forthcoming Epoch of Self-Regulating Systems - Grinin, Leonid; Grinin, Anton (2016)
Abstract: The monograph presents the ideas about the main changes that occurred in the development of technologies from the emergence of Homo sapiens till present time and outlines the prospects of their development in the next 30–60 years and in some respect until the end of the twenty-first century. What determines the transition of a society from one level of development to another? One of the most fundamental causes is the global technological transformations. Among all major technological breakthroughs in history the most important are three production revolutions: 1) the Agrarian Revolution; 2) the Industrial Revolution; and 3) the Cybernetic one. The book introduces the theory of production revolutions which is a new valuable explanatory paradigm that analyzes causes and trends of dramatic shifts in historical process. The authors describe the course of technological transformations in history and demonstrate a possible application of the theory to explain the present and forthcoming